Expansion of SLR Competencies and AI-Based Class Action Research Methods of Physical Education Teachers in Gunungpati District - Adi S; Tommy Soenyoto; Agus Darmawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Problems (1) 98% of teachers have difficulty finding literature supporting scientific work, (2) 95% of teachers have difficulty finding a more comprehensive state of the art, (3) 88% of teachers have difficulty collecting appropriate and efficient data in classroom action research, (4)) 95% of teachers have difficulty interpreting results and conclusions. Subject is an elementary school physical education teacher. Delivery methods through lectures, discussions, assignments and case methods. This activity will be carried out in 2 sessions. This activity is carried out in a hybrid basis. Session 1/day 1 is used to present material safely for 8 hours. Session 2/day 2 provides assistance to each teacher through 8 hours of practice. Then continued with online assistance. Teachers who have participated in this service can create a state of the art, make literature searches easier, understand classroom action research data collection and interpret conclusion results. These activities effectively strengthen teachers' abilities to apply sophisticated and relevant research methodologies to improve teaching practices. By integrating Systematic Literature Review (SLR) and AI technology in classroom action research, teachers can develop and implement more innovative and effective data-based teaching strategies.